Lower Arch Dimensions in Children with Anterior Open Bite and Normal Vertical Overbite: A Cross-sectional Study. (2019)
Dental arch is a dynamic structure and its size depends on genetic and environmental factors. The aim of this study was to determine lower arch dimensions in children between 8 and 16 years with anterior open bite (AOB) and normal vertical overbite (NVO).